Facts of a mixed handedness or ambidexterity - Abdullah, Nasiha; Mohd Said, Nur Shafini; Mat, Khalid Amin (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2024)
It's an amazing phenomenon in which people can utilize both their left and right hands with equal ease. Being mixed-handed can spark a world of inquiry and surprise since it contradicts conventional handedness conventions. There is an intriguing relationship between the human brain and the hands. Our minds are interconnected.